Physical Violence of Parents in Children Age School - Livana PH; Midhu Kurian; Nurnainah Nurnainah (GLOBAL HEALTH SCIENCE GROUP, 2020)
Physical violence often occurs in children, especially school-age children. School-age children are able to complete their developmental tasks if parents are able to educate children well, especially in disciplining children, but many parents choose ways to discipline children with physical violence. Physical violence by parents is able to influence the behavior and development of children, but the form of physical violence committed by parents have not been described in detail. Research aims to find out the picture of physical violence of parents in school-age children. This research is quantitative research with descriptive method. The study was conducted in the city of Kendal, Central Java, Indonesia. The study was conducted on 1313 school-age children. Data collection using total sampling techniques. The research instrument used a questionnaire. Data were analyzed univariately in the form of frequency distributions. Research results show shows that the majority of respondents were 10 years old and majority of respondents were male. Parents' physical violence in school children is shown by hitting the child with hands or sharp objects, although parents will calm the child when the child whines to ask for something. Keywords: physical violence, parent, children age school